Age-related cardiovascular risk in adult patients with congenital heart disease. (15th February 2019) - Häcker, Anna-Luisa; Oberhoffer, Renate; Hager, Alfred; Ewert, Peter; Müller, Jan
Abstract: Aims: Since the number of adults with congenital heart disease (ACHD) is increasing, age-related cardiovascular diseases become a relevant risk for ACHD. While previous studies investigated isolated risk factors only, this study examines the cardiovascular risk of ACHD based on the PROCAM scores. Methods and results: From January 2017 to April 2018, 551 ACHD aged 30 years or older (43.9 ± 9.9 years, 48.3% female) were analyzed for their risk factors of major cardiovascular events within the next ten years using the PROCAM quick check and PROCAM health check. Compared to their individual reference, ACHD had a significantly lower absolute cardiovascular event risk in PROCAM quick check (ACHD: 2.5 ± 4.9%, reference: 3.8 ± 5.2%, p < .001) and PROCAM health check (ACHD: 1.8 ± 3.5%, reference: 3.9 ± 5.3%, p < .001). The relative risk of ACHD was 37% lower than in the general population calculated with the PROCAM quick test, and 57% lower with the PROCAM health check. Only 3.4% of the ACHD had a LDL cholesterol higher than 190 mg/dl, 8.3% had a HDL cholesterol lower than 40 mg/dl, and 26.0% had triglyceride higher than 150 mg/dl. Diabetes mellitus was prevalent in 4.0% of the ACHD and 10.9% were current smokers. Conclusion: According to the PROCAM risk score, ACHD have a lower 10-year risk for major cardiovascular events compared to a healthy reference population. Whether this lower rate of the established risk factors leads to a lower rate of acquired cardiovascular disease has to be clarified in this particular population. Highlights: Adult patients with CHD have a lower 10-year risk for major cardiovascular events compared to a healthy reference 8.3% of the ACHD had a HDL cholesterol lower than 40 mg/dl, and 26.0% had triglyceride higher than 150 mg/dl Diabetes mellitus was prevalent in 4.0% of the ACHD and 10.9% were current smokers